General investigation for longitudinal wave propagation under magnetic field effect via nonlocal elasticity - Guven, U. (SHANGHAI UNIV, 2015)
In this paper, the propagation of longitudinal stress waves under a longitudinal magnetic field is addressed using a unified nonlocal elasticity model with two scale coefficients. The analysis of wave motion is mainly based on the Love rod model. The effect of shear is also taken into account in the framework of Bishop's correction. This analysis shows that the classical theory is not sufficient for this subject. However, this unified nonlocal elasticity model solely used in the present study reflects in a manner fairly realistic for the effect of the longitudinal magnetic field on the longitudinal wave propagation.
Keywords: Rayleigh-Bishop rod; nonlocal elasticity; magnetic field; wave propagation; WALLED CARBON NANOTUBES; GRADIENT ELASTICITY; ELECTRONIC-PROPERTIES; TRANSPORT-PROPERTIES; STRESS WAVES; VIBRATION; DISLOCATIONS; Mathematics; Mechanics